Study on water quality and heavy metals in relation to landuse activities of Selangor River / Md. Sadek Uddin Chowdhury - Md. Sadek , Uddin Chowdhury (2017)
The Selangor River is very important from the viewpoint of water supply and multipurpose water use in Malaysia. Rapid development, population growth, urbanization and industrialization are being undertaken in the state of Selangor and the city of Kuala Lumpur, Malaysia. As a result of these changes, the character of the major pollutant sources may evolve from rural type sources to industrial type sources, which results in many environmental troubles and contradictory interests of water users. This study focuses on a comprehensive water quality assessment and models the impact of point and non-point sources of pollution on the Selangor River water quality. Water quality Index (WQI) consists of six parameters, viz. DO, pH, BOD, COD, AN, TSS and it is used to define the status of river water quality. Thirteen heavy metals viz. Arsenic(As), Aluminum(Al), Cadmium (Cd), Chromium (Cr) , Copper (Cu), Cobalt (Co), Iron(Fe), Lead (Pb), Magnesium (Mg), Manganese (Mn), Nickel (Ni), Silver (Ag) and Zinc (Zn) were analysed using inductively coupled plasma optical emission spectroscopy (ICP-OES). Total coliform and Escherichia coli (E.coli) were analyzed for microbial pollution assessment. In order to predict and assess the water quality status in Selangor River basin, QUAL2K was used as a simulation model. Water quality parameters DO, BOD and NH3-N have been chosen for modeling. In addition, different model scenarios were simulated in order to assess the impact of point and non-point sources on the Selangor River water quality. The results showed that Selangor River is affected in terms of high concentrations of COD, BOD and NH3-N. Most of the stations in these river basins recorded water inferior to Class III. Significantly lower water quality was found in areas downstream from high human impact areas, where urban land was dominant or near point sources of pollution. The water quality parameters exhibited significant variation between built-up and mining sites. The Rawang sub-basin within the study area was identified as the main contributor of pollutants. A river pollution level map was developed based on this information for better visualization and spatial indication of the polluted areas. Metals analysis showed As, Mn and Fe exceeded the admissible limit of Malaysian National Standard Water Quality at some of the sampling stations. Heavy metal pollution index (HPI) was below the critical pollution index value of 100. Anthropogenic metal concentrations in the Selangor River water were low, indicating that the Selangor River does not experience extreme pollution. Concentration of ions viz. sodium, potassium, calcium and nitrate were significantly high in some tributaries, whereas forested areas showed low values of these parameters. The highest E.coli was found in the urban area followed by industry, residential and agricultural area respectively. The water quality model presented different scenarios for changes of Selangor River water quality. From scenarios it was found that, the river water quality issue in the Rawang sub basin within the study area is considered crucial to create significant improvement within the sub basin and in the downstream area of Selangor river basin. Key words: Water quality, Heavy metal, Land use, Pollution, Selangor River, WQI, GIS, QUAL2K.